Development of a novel computational fluid dynamics-based model for a solar photovoltaic/thermal collector-assisted domestic hot water system with sensible heat storage. (25th June 2023) - Kalkan, Cem; Duquette, Jean; Akif Ezan, Mehmet
Highlights: A novel computational fluid dynamics-based algorithm is developed. Finned and unfinned collectors are compared using air and water as working fluids. The solar fraction, electricity fraction, and utilization factor are evaluated. The highest solar fraction is reached when using an air-based finned collector. This system is the most effective for meeting concurrent heat and power loads. Abstract: This study proposes a novel numerical modelling approach to investigate the dynamic performance of a solar photovoltaic/thermal domestic hot water system. A three-dimensional numerical model of a flat-box solar collector developed in ANSYS-Fluent is coupled with a reduced one-dimensional model of all other system components. Coupling these models allows for a more accurate evaluation of the system's overall performance as consideration is given to both the spatial variations inside the collectors, and the overall system's temporal response. The city of Ottawa, Canada is used as the case study location and a monthly comparison is made between scenarios comprising two different working fluids ( i.e. air and a water-ethylene glycol solution) and two photovoltaic/thermal collector design alternatives ( i.e. with and without fins). To assess the performance of each scenario, the solar fraction, electricity fraction, and utilization factor are computed. Results show that the solar fraction is greater in the air-based system than in the water-based system for all months of the year, and values as high as 90.1% and 84.3% are obtained, respectively. Similarly, the addition of fins to these systems is shown to improve the solar fraction on an annual basis by 7.4%, and 1.4%, respectively. Similar trends are observed for the utilization factor, which indicates that the air-based system with fins is the most effective system with regards to utilizing incident solar radiation for meeting simultaneous heat and power loads. The annual average electricity fraction, on the other hand, shows little variation between scenarios on a month-by-month basis, which leads to the conclusion that adding fins and/or changing the working fluid has a negligible effect on the electrical performance of the system.